Mathematical model of hiring a new lecturer / Nur Idalisa Norddin, Khlipah Ibrahim and Ahmad Aziz - Norddin, Nur Idalisa; Ibrahim, Khlipah; Aziz, Ahmad (Research Management Institute (RMI), 2012)
In the educational system, lecturers play important role in producing marketable graduates. This can be achieved by employing potentially competent lecturers. As being practiced in Universiti Teknologi MARA (UiTM), the process of selecting new lecturers involves three phases: academic qualification, mock teaching and face-to face interview. In UiTM, the candidates will be shortlisted after performing the mock teaching session. Then, the shortlisted candidates will be called for the face-to-face interview. This paper proposes a selection model based on Analytical Hierarchy Process (AHP), which uses both qualitative and quantitative decision making approaches. This model contains 5 levels of hierarchy, starting with the goal (new lecturer), 3 types of interview, 13 criteria of the interview, 8 sub-criteria, and finally the candidates.